Computational Complexity Comparison between DC-biased Optical OFDM and Asymmetrically Clipped Optical OFDM in Visible Light Communication - Shrestha, Sunil Kumar (Journal of Science and Engineering, 2023)
Optical wireless systems are constrained to send real and positive values to the optical transmitter as only intensity of a signal is used to carry information. Therefore, conventional OFDM cannot be directly applied in optical systems. To combat multipath distortion, several modified OFDM systems have been studied, such as DC-biased optical OFDM (DCO-OFDM) and asymmetrically clipped optical OFDM (ACO-OFDM). In order to transmit real signal in optical environments, there is a Hermitian symmetric constraint with Discrete Fourier transform (DFT). This paper compares transceiver complexity of ACO-OFDM with that of DCO-OFDM which is used in Visible Light Communication (VLC), and it is found that for the same number of subcarriers, computational complexity is higher in ACO-OFDM.